The medico-legal and ethical considerations associated with intraoperative neurophysiological monitoring in the USA: overview and proposed guidelines for legal and risk management professionals. (1st January 2013) - Wiggins, Michael; Sherman, John; Pierson, Steve
Intraoperative neurophysiological monitoring, known by the acronym IONM, is a method for monitoring and recording the inner neurological activity of a patient undergoing surgery. When using conventional means of monitoring, neurological damage during surgery may go undetected. IONM prevents this by indicating what is going on within a patient, often in real time, enabling surgeons to change course during surgery. Although IONM offers benefits, its use should not be undertaken without regard to the legal and regulatory issues involved. These include contractual, malpractice, and products liability concerns. In the USA, where healthcare providers are seen as 'deep pockets', these issues must be approached with due care. Healthcare risk-management professionals should take precautions that ensure IONM use will be efficacious and utilised in a manner that minimises the risks inherent in the introduction of new technologies into heavily litigated fields. This paper provides professionals with legal strategies for accomplishing this task.